Giant melanocytic nevi and soft tissue undergrowth in the left leg: pathogenetic hypothesis - Piero Pavone; Raffaele Falsaperla; Silvia Marino; Martino Ruggieri; Andrea D. Praticò; Beatrice Nardone (MDPI AG, 2019)
Congenital melanocytic nevi (CMN) are observed frequently in children. The anomalous skin shows a widely variable clinical expression not only in the anatomic location, but also in color, morphology and superficial structure. According to the width CMN are distinguished in small, medium, large or giant. Aside the cosmetic problem and its psychological implications, CMN may present with severe complications consisting of malignant transformation and/or central nervous system involvement. We report on a 3-month old infant with an extensive CMN in the left leg, which extended from the lower portion of the knee to the foot, with satellite nevi. Concomitant with the extensive nevi in the same district a remarkable reduction in size was present, and involved the adipose and muscle tissues, contributing to a counterpart diameter difference of 5 cm, without bone involvement. Melanocytic nevi and soft tissue undergrowth in the leg is an usual association; a pathogenic explanation on the anomaly involving concomitantly the skin and the underneath soft tissues is advanced.